Knowledge, Attitude and Ethical Perception Regarding Organ Donation among Undergraduate Students of a Medical College at Biratnagar, Nepal - Katwal, Barsika; Kandel, Jwala; Limbu, Manoj Hang (Journal of Nobel Medical College, 2026)
Background: Organ donation; a community service that saves lives have been the subject of extensive interest both nationally and internationally over the past decade. Transplantation is the only form of treatment for people with life-threatening diseases and injuries. Even though Organ Transplant Act Nepal 2016 has opened doors for the cadaveric organ donation and transplantation, till date only limited transplant has been done. This study aimed to understand public sentiment and different barriers toward organ donation from the perspective of medical students in Nepal. Methods and Methods: A cross-sectional study was conducted among medical students of Nobel Medical College, Biratnagar, Nepal, from September 2025 to April 2026. The study included undergraduate medical students, willing to participate. The questionnaire was distributed through online portal to the students after providing the necessary instruction and explaining the study in detail. Results: This study assessed the knowledge and attitudes regarding organ donation among undergraduate medical and nursing students (n=205) at a medical college in eastern Nepal. The findings demonstrated a moderate level of knowledge (mean score: 10.3 ± 2.0 out of 15) and a generally positive attitude toward organ donation (mean score: 46.6 ± 5.1 out of 60). Conclusion: Undergraduate medical and nursing students demonstrated moderate knowledge and positive attitudes toward organ donation. Significant differences in knowledge were observed by gender and in attitudes by ethnicity, highlighting the need for targeted educational and awareness programs to further promote organ donation among future healthcare professionals.